Factors Affecting Return Share Of Mudharabah Deposits Sharia Commercial Banks - Inda Arfa Syera; Hajar Affiah (Publisher Cv. Inara, 2021)
The specific purpose of this study is to determine the factors that affect the return for the results of Islamic Bank deposits. The approach used in this research is a quantitative approach. The data used in the form of secondary data in the form of time series originating from the website of the Financial Services Authority (OJK) with the link www.ojk.go.id regarding the amount of return for mudharabah deposit results, Capital Adequacy Ratio, Non Performing Financing, Financing to Deposit Ratio and Inflation originating from the website of Bank Indonesia (BI) with the link www.bi.go.id. The population is monthly data from January 2016 to December 2019 period while the sample is annual data from 2016 to 2019. The research analysis conducted is multiple linear regression, classical assumption test (normality test, heteroscedasticity multicollinearity test and autocorrelation test), and test statistics (coefficient of determination (R2), statistical F test, and statistical t test). The results of this study are the variables of Capital Adequacy Ratio, Non-Performing Financing, Financing to Deposit Ratio and Inflation have a significant effect simultaneously (simultaneously) on the variable of Profit Sharing for Mudharabah Deposits for Islamic Commercial Banks.